KETERKAITAN ANTARA MANAJEMEN LEMBAGA & MANAJEMEN PEMBELAJARAN TERHADAP PENDIDIKAN KEAGAMAAN DAN PONDOK PESANTREN - GUNAWAN GUNAWAN (Universitas Islam Negeri Sumatera Utara, 2019)
Islamic boarding schools, schools and madrasah are institutions that have the same purpose but are different in their management and each has its own characteristics. In the midst of differences and similarities from existing educational institutions, there is little competition between existing educational institutions. The role and existence of Islamic boarding schools as one of the original Indonesian educational institutions indeed must be preserved and noted for their development, because the presence of Islamic boarding schools in the midst of society is in addition to empowering the community as a place to prepare Ulama cadres who are able to master and understand Al- The Qur'an and al hadith are good and true and according to the needs of the community. According to KH. Abdurahman Wahid that the scientific tradition of Islamic boarding schools cannot be separated from the intellectual struggle that occurred throughout the history of the development and expansion of Islam.